Collaborative Telehealth Intervention for Performance of Activities During Daily Routines by Children and Adolescents with Physical Disabilities: A Feasibility Study. - Matey-Rodríguez, Carmen; Pico, Mónica; Robles-García, Verónica; Musso-Daury, Lisa; Santos-Lozano, Alejandro; Palisano, Robert J. (Physical & Occupational Therapy in Pediatrics, 2026)
Aim: To evaluate the feasibility and effectiveness of a collaborative telehealth intervention on engaging families in the intervention process, achievement of individualized goals, time spent practicing goal activities, and participant experiences. Methods: Twenty-one children/adolescents with physical disabilities (mean age 10.6 ± 4.1 years) and their parents collaborated with a physical therapist on an eight-week individualized intervention to achieve three goals for performance of activities during daily routines using WhatsApp. Results: Mean ratings for Performance and Satisfaction with performance on the Canadian Occupational Performance Measure and mean Goal Attainment Scale T-scores increased between baseline, post-intervention, and 12-week follow-up (p < 0.001). Participants reported the intervention was more practical than usual care, they practiced their goals during the intervention, continued to practice in the 12 wk until follow-up, and the intervention empowered them to plan new personal goals in the future and ask for help when needed. An average of 9.2 ± 4.5 h was spent practicing the activities for the three goals. Conclusions: The collaborative process facilitated family engagement in the intervention and may have potential to build family capacity and children's self-determination. Further research is needed to determine whether the findings are replicable when the intervention is incorporated into students' education programs. Trial Registration: Registered July 2024 at clinicaltrials.gov (NCT06514287)